Developing EASPod as a Medium for English Academic Speaking for Mahasantri - Fachriza, Aries (ELLITE, 2023)
Podcasting is kind of digital media allows someone to produce and listen to content on   variety of topics. podcasting can assist learning materials in   field of education and language especially developing English Speaking skills. This research aims to develop EASPod to enhance students’ speaking skills. This development research employed ADDIE model namely Analyze, Design, Develop, Implement, and Evaluate. The subjects were 36 students or Mahasantri in the third semester, Department of English Language Teaching, University of Darussalam (UNIDA) Gontor.   Data collection technique in this research was questionnaires, observation, pre- and post- test (podcasting 1 and podcasting 2) while the data analysis technique is descriptive and inferential statistics. The result is to produce audio and video podcasts to improve students’ spoken skills in the academic field   producing types of academic English conversation. The development of EASPod has been implemented in the English Language teaching department in producing academic-speaking podcasts. This Application is also gaining valid criteria from the experts.  The potential effect of this implementation is students’ improvements in speaking skills proven by the Average score of speaking post-tests were higher than its pre-test. They increased by 6,64 %.  p Value is 0,000. if significant value ( p) less than  0,05, it indicated improvement between podcasting 1 and podcasting 2 . These activities also rise students’ confidence and students’ accuracy of vocal use and articulation in practicing academic speaking. It means that podcasting in EASPod has been successfully applied in supporting English Academic Speaking for university students in Pesantren Based-University.